Pengaruh Kompos terhadap Kecernaan Bahan Kering dan Organik Rumput Hymenachne amplexicaulis (Rudge) Nees - Akmal Akmal; Hardi Syafria; Riyan Ananda Putra (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Compost fertilizer can overcome the problems found in red-yellow podzolic soil, namely the low availability of nutrients and less able to hold water. The purpose of this research was to prove the impact of composting on dry matter and organic matter digestibility of kumpai grass planted on red-yellow podzolic soil. The research design used was a randomized block design (RAK) with 4 treatments and 5 replications, namely K0 (control) = 0 Kg/4m2, K1 = 4 Kg/4m2, K2 = 8 Kg/4m2, K3 = 12 Kg/4m2. The observed variables were pH (degree of acidity) of the supernatant, dry matter digestibility (KcBK), and organic (KcBO). Based on the analysis variance or variance, it showed that the application of compost had no significant effect (P>0,05) on the pH value of the in vitro supernatant, but it had a very significant effect (P<0,01) on the dry matter and organic digestibility of kumpai grass. Based on Duncan’s real distance difference test, the compost treatment of 12 Kg/4m2, showed the highest dry matter and organic matter digestibility compared to the compost treatment of 0 Kg/4m2, 4 Kg/4m2, and 8 Kg/4m2, namely 43,04% and 44,32%.